Tasaday scandal ; The lost tribe [videorecording] - Edwards, John.; Taylor, Ian. ([S.l.] Thames Production, 1987)
A story of the Tasaday scandal in Southern Mindanao and the claim of Manuel Elizalde, Jr. for discovering this tribal people who are really Manobos and T'bolis.
Tasaday scandal (50 min.) -- The lost tribe (20 min.)
Film editor, Barbara Farmer; Reporter, Philip Tibenhan; Researchers, Adrian Wood
Keywords: Elizalde, Manuel, Jr; Tribes -- Philipines -- Mindanao; Anthropology; Philippine history